Radical right-wing support among urban voters in Germany: Disentangling the roles of immigration, immigration history, segregation, and poverty in the neighborhood - Katja Salomo; Marcel Helbig; Susanne Marquardt (Journal of Urban Affairs, 2025)
We examine how Germany's largest wave of immigration in recent history contributed to the election of a radical right-wing party (AfD) to the German parliament for the first time since the end of World War II. We focus on urban voters and use unique data from 34 of Germany's largest cities, divided into 1,905 neighborhoods, covering 2014–2017. We find that local poverty strengthens the AfD, while greater local immigrant presence weakens AfD support. Immigrants are more concentrated in poorer neighborhoods, but crucially, local poverty does not undermine the effect of immigrant presence. Immigrant concentration in poorer neighborhoods indirectly increases AfD support in advantaged neighborhoods. The latter offer fewer opportunities for intergroup contact and are less likely to have prior meaningful history of immigration, rendering their residents more vulnerable to acculturative stress. Indeed, very low prior shares of immigrants predict higher AfD support when the local share of immigrants suddenly increases.
Keywords: 330; Radical right; voting; neighborhood; poverty; segregation; acculturative; stress; halo effect